From words to deeds: when digital app acceptance turns into sustainable mobility behaviours. Methodologies and insights from MaaS experiences - Valentina Costa; Ilaria Delponte (Urban, Planning and Transport Research)
Mobility-as-a-Service (MaaS) is typically framed as a tool that offers multi-modal transportation solutions through an integrated digital interface, playing a pivotal role in supporting the sustainable transition within Smart Cities. However, its applications and user acceptance are often assessed from a narrow, mobility-focused perspective, which tends to reduce the MaaS experience to a purely travel-related service – thus overlooking its broader potential. Users’ preferences, willingness-to-adopt, and willingness-to-pay are commonly evaluated based on factors such as transportation service performance, fare schemes, and convenience. However, when considering the deeper mindset and behavioral shifts required for the adoption of more sustainable transportation modes, the tools implemented must not only be functional but they must also resonate with how users perceive and interact with them. These interactions are crucial for the success and widespread adoption of MaaS solutions. This paper reviews the primary methodologies used to evaluate MaaS acceptance, highlights their strengths and limitations, and explores the role of digital platforms in facilitating the shift toward sustainable mobility. The main focus will be represented by the potential benefits to MaaS successful implementation that can arise from optimizing users’ digital experiences, particularly through the integration of nudging and rewarding systems designed to influence individual behavior.